2014
DOI: 10.1051/nss/2014025
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnologies : l’espace civique des risques technologiques redimensionné

Abstract: Après l'avènement de la « société du risque », serions-nous entrés dans une nouvelle ère, marquée par l'émergence d'un espace civique caractérisé par une dilution des frontières traditionnelles entre monde syndical, société civile et recherche ? C'est la thèse défendue par les auteurs de cet article qui analysent les débats sur la sécurité des nanotechnologies. Les auteurs pointent assez justement l'importance du niveau européen comme espace de déploiement de cet espace civique. Mais cela ne doit pas conduire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Thus, we can observe a tension between, on the one hand, the widely accepted particularities of the risks of nanotechnologies, and, on the other hand, the standardization of methods for handling them in workspaces. Indeed, debates over nanomaterials have shown that they cannot be evaluated using the classical principle of the dose-effect relation, but rather that risk prevention must be based on the precautionary principle Chaskiel and Suraud (2014). Nevertheless, in terms of administrative and medical oversight, management of the occupational risks of nanomaterials appears non-speci ic, even banal.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can observe a tension between, on the one hand, the widely accepted particularities of the risks of nanotechnologies, and, on the other hand, the standardization of methods for handling them in workspaces. Indeed, debates over nanomaterials have shown that they cannot be evaluated using the classical principle of the dose-effect relation, but rather that risk prevention must be based on the precautionary principle Chaskiel and Suraud (2014). Nevertheless, in terms of administrative and medical oversight, management of the occupational risks of nanomaterials appears non-speci ic, even banal.…”
Section: Introductionmentioning
confidence: 99%